Supply Chain Path Dependency in Collaboration for New Product Development - Ettlie, John; Murthy, Rajendran (Management Science Research Journal, 2026)
This study examines the relationship between partnership structuring dynamics and performance, focusing on integration in co-development partnerships. Through a detailed survey, insights were gleaned from experts in collaborative engineering engaged in NPD. The analysis juxtaposes levels of partnership—synchronized, coordinated, and integrated—with operation, innovation and market performance. Results reveal that early-stage synchronization impacts operational performance more than later stages, and integration enhances innovation and market performance. Further, a post-hoc assessment links integration with vital financial outcomes to validate these findings. Employing resource orchestration theory, this research illustrates the influence of co-development structuring nuances on firm performance, emphasizing the critical balance between path dependency and creation.